Cardiovascular Hyperreactivity and its Association with Cardiovascular Risk Factors - Milagros Lisset León Regal; Mikhail Benet Rodríguez; Yudith Brito Pérez de Corcho; Lázaro Hermes González Otero; José Omar de Armas García; Luciano Miranda Alvarado (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Background: several studies show a relationship between cardiovascular hyperreactivity and cardiovascular risk factors. However, finding new evidence to corroborate. Objective: to determine the association between cardiovascular reactivity and cardiovascular risk factors in normotensive individuals. Methods: a cross-sectional, correlational study was conducted in a universe composed of the population aged 15 to 74 years in the urban area of Cienfuegos municipality. The sample included 644 people studied in 2010. The variables analyzed were: sex, skin color, age, height, weight, body mass index, waist circumference, triglycerides, cholesterol, HDL cholesterol and fasting blood glucose. Chi-square and prevalence ratio with a 95 % confidence interval were calculated. Results: the prevalence of cardiovascular hyperreactivity was 42.3 %. A prevalence ratio of 51.3 % in men and 36.8 % in women was observed and it exceeded 65 % in individuals older than 64 years. It increased with age. Highest percentage of hyperreactivity was found in obese and overweight individuals. Triglyceride levels associated with cardiovascular hyperreactivity were also significant. Conclusions: there is an association between cardiovascular hyperreactivity and cardiovascular risk factors such as obesity, hypertriglyceridemia and hypercholesterolemia in normotensive individuals, a situation still observed in non-obese individuals.